Construction of Shared Semantic Spaces through Gestures in Interpreter-Mediated Psychotherapy Sessions - Chwalczuk, Monika (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Gestures are an inherent part of all face-to-face interactions. Nevertheless, their role in interpreter-mediated events has so far been marginalized in the field of interpreting studies. Based on a multimodal corpus of interactions in child psychiatry with migrant patients, this research focuses on the use of iconic gestures, their role in bridging the linguistic gap and in performing cultural mediation. The results of the study suggest that gestures play a part in the construction of shared semantic spaces and act as a marker of interpreting fidelity, hence, becoming corner stones in the trust-building process between the migrant patients and the public service interpreters.